BEBERAPA FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI TINGKAT ADOPSI PANCA USAHA PETERNAKAN SAPI PERAH - Kusumahadi, Didik (Universitas Tribhuwana Tunggadewi, 2008)
The purpose of this research was to elucidate the adoption grade of “Panca Usaha” of milking cow farmers and economic social factors influencing the adoption grade of “ Panca Usaha Peternakan sapi perah”. This research was a case study executed by survey technique in Pacet District of Mojokerto Regency. Samples of the research were 80 milking cow farmers that were selected using a stratified random sampling method. The data was analyzed using Rank Spearman’s correlation method and linear multiple regression model. The results showed that the adoption grade of cattle farmers was very much influenced by variables of education and knowledge. Cattle farmer’s grade adoption of “Panca Usaha” was distributed with high adoption grade of 10%, medium adoption grade of 68,75%, and low adoption grade of 21,25%. Intensity and quality dimensions of stratum I adoption grade were 2,5% high adoption, 10% medium adoption and 2,5% low adoption, while those of stratum II were 15% high, 45% medium and 0% low adoption